HSCT FOR PEDIATRIC DISEASES - Seber, Adriana; Gomes, Alessandra; Vieira, Ana Karine; Rodrigues, Ana Luiza Melo; Silva, Ana Maria Marinho da; Zanette, Antonella; Macedo, Antonio Vaz de; Breviglieri, Carla Nolasco Monteiro; Zanchetta, Carla; Bonfim, Carmem; Kuwahara, Cilmara; Carvalho, Cinthya Rocha; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION